2021
DOI: 10.1097/mao.0000000000003195
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Evaluation of Minimally Invasive Ponto Surgery With a Modified Drill System for Inserting Bone-Anchored Hearing Implants

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
(69 reference statements)
3
7
0
Order By: Relevance
“…MIPS represents a promising minimally invasive, punch-only, surgical technique for BCD implantation. Comparable or improved soft tissue outcomes in combination with better results registered in surgical time, cosmetics, skin sensibility and in the field of cost analysis compared with the outcomes of traditional techniques can corroborate this statement ( 25 29 , 32 , 33 , 37 ). These encouraging features make this technique relevant to improve and to further streamline the procedure to install a BCD.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…MIPS represents a promising minimally invasive, punch-only, surgical technique for BCD implantation. Comparable or improved soft tissue outcomes in combination with better results registered in surgical time, cosmetics, skin sensibility and in the field of cost analysis compared with the outcomes of traditional techniques can corroborate this statement ( 25 29 , 32 , 33 , 37 ). These encouraging features make this technique relevant to improve and to further streamline the procedure to install a BCD.…”
Section: Discussionmentioning
confidence: 78%
“…Since the introduction of MIPS, the drill components in the surgical kit have been updated with the aim of reducing the heat generated during drilling ( 36 ). A recent clinical study reported a trend toward an improved implant survival rate using this updated MIPS system in comparison with the original drill system ( 37 ).…”
Section: Introductionmentioning
confidence: 97%
“…This scenario showed a €62.49 difference in mean cost per patient between both techniques in favor of the MIPS after complete follow-up (Table 3). In the final scenario, the more realistic implant loss of 4.0% for the MIPS was used, based on the latest study using the modified MIPS drill system (36). This more representative number of implant loss showed a difference in mean cost per patient of €154.43 in favor of the MIPS (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the MIPS was introduced only shortly before the start of this study, so this MIPS cohort reflects the first group of procedures and patients operated on with the MIPS. A recent study of Caspers et al (36) showed that implant loss with the MIPS using the new modified drill system is only 4.0%. Reduced implant loss will lead to lower costs per patient for the MIPS and an even larger difference between the MIPS and the LITT-P.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation